The distribution of Mallard ringed in southern England - Boyd, H; Ogilvie, M A (Wildfowl, 1961)
Recoveries of Mallard ringed at six stations in the south of England from 1947 to 1960 are used to study the homogeneity of the population. A large majority of the ducks were ringed in the months August-November and very few in the breeding season. Little emigration of autumn-marked Mallard occurs during the winter, though some move to France. Within Britain dispersal is usually over quite short distances. Circles of 10 miles radius around the three major stations (Abberton, Essex; Borough Fen, Northants; and Slimbridge, Glos.) include 81 (63%), 99 (22%) and 43 (22%) direct recoveries (in the same season). The ’winter dispersion areas’ of the three stations, defined as the areas containing the nearest 90% of direct recoveries, cover about 2,200, 13,800 and 10,500 sq. miles, with comparatively little overlapping. Recoveries in the breeding season (February to July in England) are much less plentiful than those in the shooting season, but they show a pattern of distribution similar to the ’winter dispersion areas.’ The proportions of recoveries in England in later winters which are within the dispersion areas are very high: 86%, 86% and 85%. Smaller-scale ringing in Norfolk and Dorset confirms that most surviving Mallard remain in, or return to, their winter homes. The winter population of Mallard in southern England includes immigrants drawn from a large area around the Baltic and from west Germany, Holland and northern France. The proportion of visitors from abroad seems to vary considerably from place to place. Precise estimates are impossible from the available data but it seems that about half the Mallard sampled in Essex which survive the winter emigrate the next spring. The corresponding fractions for Borough Fen and Slimbridge, though uncertain, are substantially less. No differences in the summer distribution of recoveries abroad are apparent. In the autumn after ringing the proportion of Essex-ringed Mallard taken in Holland is higher, and that of Borough Fen and Norfolk-ringed birds lower, than the average, suggesting that in the later stages of autumn migration some differentiation of routes occurs. No differences in the summer ranges of males and females are apparent.